UV-VIS detection of amino acids in liquid chromatography: online post-column solid-state derivatization with Cu(II) ions - Kubíčková, Anna; Kubíček, Vojtĕch; Coufal, Pavel (Journal of separation science, 2011)
In this work, we describe the introduction of a post-column solid-state reactor in the HPLC system used for the analyses of amino acids. The reactor used was filled with copper(II) oxide. Passage of the analytes through the reactor leads to the formation of Cu(II) complexes. Unlike free amino acids, the Cu-complexes show significant absorbance in the UV region and accordingly sensitivity of UV-VIS detection is increased by two to three orders of magnitude. As a result of this improvement in sensitivity, we have obtained LOD values in micromolar range and good linearity over the studied concentration range (5.0×10(-5) to 2.0×10(-3) mol/L). The method exhibits advantages typical of solid-state reactors, such as negligible loss of efficiency due to the derivatization, simplicity of realization and a long-term durability. The presented system brings an easy and versatile solution for UV-VIS detection of coordinating compounds, which do not normally absorb well in the UV-VIS region.
Keywords: Spectrophotometry; Copper; vysokoúčinná kapalinová chromatografie; Amino Acids; Chromatography, High Pressure Liquid; aminokyseliny; spektrofotometrie ultrafialová; spektrofotometrie; Spectrophotometry, Ultraviolet; měď